Implementing a circular business model for reusable packaging : Multidisciplinary learnings from reusable pizza packaging - Tenhunen-Lunkka, Anna; Balatsas-Lekkas, Angelos; Mouazan, Erwan; Palola, Sarianna; Ngo, Tran; Salo, Minna; Hylkilä, Eveliina; Sundqvist, Henna; Luomala, Harri; Pennanen, Kyösti; Sorvari, Katariina; Petänen, Päivi; et al. (Elsevier, 2024)
This article explores practical challenges in developing and implementing circular business models in the context of reusable takeaway food packaging from a transdisciplinary perspective. It touches upon the desirability, feasibility, viability, and sustainability dimensions of a reusable pizza packaging circular business model. First, a literature review is conducted to highlight current knowledge and gaps around circular business models for reusable packaging and the key factors addressing the desirability, feasibility, viability, and sustainability. Second, a case study approach is taken for an in-depth exploration of these factors and their effect on the successful implementation of a reusable packaging business model. A real-life pilot is structured and implemented; questionnaire, workshops and semi-structured interviews with consumers and key stakeholders of the novel business model as well as technical laboratory tests of used packaging are used as key data sources in the case study. This study contributes to research and practice with a novel framework for circular business model innovation in the context of reusable packaging highlighting the need to iteratively address packaging as well as system conditions affecting the desirability, feasibility, sustainability, and viability of such ecosystem-based business models. Future research should inherently take a systemic perspective to address interconnections between these four dimensions and explore in which steps and order experimentations should be developed to balance trade-offs between feasibility and desirability while ensuring sustainability and viability of the business model.
Keywords: Reusable packaging; Circular business models; Takeaway food packaging; Conceptual framework; circular economy; sustainable consumption; fi=Markkinointi|en=Marketing|